Assessing Affective Domain in PAI Subjects: A Case Study of SD Negeri 19 Tanah Jambo Aye, North Aceh District - Fitri, Hazal; Azmi, Ulil; Yusmanita, Sarniyati (Lembaga KITA, 2023)
Teachers at SD Negeri 19 Tanah Jambo Aye, North Aceh District are tasked with being able to measure the competencies that have been achieved by students. Teachers must also carry out their duties as teachers, namely evaluating assignments given over a certain period. The aim of this research is to find out: (1) Implementation of evaluation of affective learning components. 2) The process of implementing affective evaluation in the subject. 3) Assessment of PAI teaching objects. This research uses a descriptive method with a qualitative approach. The data collection techniques used were observation, interviews, and documentation studies. The research subjects were 1 teacher, 1 principal, and 35 students. Research results: (1) Implementation of student affective evaluation at SD Negeri 19 Tanah Jambo Aye, North Aceh district shows that students on average receive good behavior scores because of observations, with attitudes that have changed in class. The report is submitted to the teacher and principal. (2). According to observations from the Implementation Process, students' emotional assessment in receiving lessons from the teacher, students' attention to what the teacher explains, students' appreciation for the teacher, the desire to ask the teacher to be active in group discussion forums and the desire to learn more lessons, better than before. (3). Evaluation of PAI Subjects in class VIa results in students mastering Islamic teachings and making them a source of values, guidelines and basics of thought and behavior in applying knowledge and professions that follow, making the